1992
DOI: 10.1177/036354659202000117
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a meniscal prosthesis on knee biomechanics and cartilage

Abstract: A meniscal prosthesis made of Dacron with polyurethane coating was tested as a substitute for the medial meniscus in a rabbit experimental model concentrating on biomechanical behavior of the knee joint and gross and histologic evaluation 3 months after surgery. The results were compared to sham-operated knees, knees with a peripheral incision of the medial meniscus, and knees with a total meniscectomy. Knees with prosthesis implantation had the same stiffness as knees with sham-operation or meniscal incision,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0
1

Year Published

1993
1993
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(16 citation statements)
references
References 26 publications
0
15
0
1
Order By: Relevance
“…It has been accepted that meniscal lesions in the vascularized portion of the meniscus heal, whereas lesions in the avascular portion of the meniscus do not repair 28–30. Numerous strategies to repair and replace the meniscus have achieved only limited success 31–35. In a previous study, we achieved a successful repair of large meniscal defects that included both the vascular and avascular zones using a mesenchymal stem cell‐matrix combination 7.…”
Section: Introductionmentioning
confidence: 94%
“…It has been accepted that meniscal lesions in the vascularized portion of the meniscus heal, whereas lesions in the avascular portion of the meniscus do not repair 28–30. Numerous strategies to repair and replace the meniscus have achieved only limited success 31–35. In a previous study, we achieved a successful repair of large meniscal defects that included both the vascular and avascular zones using a mesenchymal stem cell‐matrix combination 7.…”
Section: Introductionmentioning
confidence: 94%
“…In the medial compartment, degenerative changes appear to be proportional to the amount of menisci removed and the postoperative period. Several in vivo studies demonstrated that chondral lesions appear earlier and more intensively in the tibial plateau than in the femoral condyle 7, 8. Therefore, a medial meniscectomy in animals is frequently used as a model for knee osteoarthritis 9…”
mentioning
confidence: 99%
“…The first study on the rabbit model dates back to 1992 [ 21 ], when a Dacron meniscus prosthesis with polyurethane coating was used. Results of this trial were fairly negative, since poor tissue healing was observed, with low scaffold integration, and the meniscal substitute did not prevent cartilage degeneration with respect to the meniscectomized control group.…”
Section: Resultsmentioning
confidence: 99%